Vaginal hygiene to prevent postoperative complications in various gynecological diseases - I.B. Manukhin; E.I. Manukhina; I.R. Safaryan (LCC «Medicine-Inform», 2021)
I.B. Manukhin, E.I. Manukhina, I.R. Safaryan A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow, Russian Federation Aim: to assess the efficacy of vaginal care hygiene in women with various gynecological disorders requiring surgical interventions to reduce postoperative complications. Patients and Methods: eighty women aged 39-60 with various gynecological diseases diagnosed with vaginal microbiota abnormalities (E.F. Kir vaginal smear cleanliness grade 3-4) during the preoperative evaluation before a scheduled surgery underwent a complex clinical laboratory examination and treatment. The study group included 60 women who received a complex vaginal preparation containing 100 mg metronidazole and 100 mg miconazole nitrate (1 capsule at night) plus oral metronidazole (500 mg daily) five days before and after surgery. In the control group, vaginal hygiene was performed according to the general management standards (vaginal chlorhexidine 16 mg twice daily or oral metronidazole 500 mg daily for five days) in the presence of complaints and/or abnormalities in vaginal smears identified b y microscopy. Results: 14 days after surgery, normal vaginal microbiota was reported in all study group women (vaginal smear cleanliness grade 1-2), while in the control group, vaginal smear cleanliness grade III-IV was reported in 8 women. Postoperative complications occurred in the control group only, i.e., two women were diagnosed with postoperative wound dehiscence after procedures for genital prolapse and two women were diagnosed with subacute infectious inflammatory pelvic disorders. Conclusion: our findings show the efficacy of vaginal hygiene with a complex vaginal preparation before and after pelvic floor surgery, as demonstrated by preventing bacterial vaginosis recurrences and reducing the rate of postoperative complications. Keywords: bacterial vaginosis, vulvovaginal candidiasis, vaginal infection, postoperative complications, vaginal hygiene, metronidazole, miconazole. For citation: Manukhin I.B., Manukhina E.I., Safaryan I.R. Vaginal hygiene to prevent postoperative complications in various gynecological diseases. Russian Journal of Woman and Child Health. 2021;4(4):322-327 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-322-327.